2006
DOI: 10.1158/1055-9965.epi-06-0381
|View full text |Cite
|
Sign up to set email alerts
|

XRCC1, XRCC3, and XPD Polymorphisms as Modifiers of the Effect of Smoking and Alcohol on Colorectal Adenoma Risk

Abstract: Using a sigmoidoscopy-based case-control study (753 cases, 799 controls) in Los Angeles County, we investigated the potential modifier role in the effect of alcohol and smoking of single-nucleotide polymorphisms (SNP) in three DNA repair genes, XRCC1 (Arg194Trp and Arg399Gln), XRCC3 (Thr241Met), and XPD (Lys751Gln). We have previously reported an inverse association between the XRCC1 codon 399 SNP and adenoma risk among these subjects. We now report that subjects with the XPD Gln/Gln genotype were inversely as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 47 publications
2
38
1
1
Order By: Relevance
“…Therefore, the results observed in this study might be driven by this SNP, which was not investigated. A causal role of the codon 280 SNP and differences in LD patterns between Singapore Chinese and U.S. subjects also could explain the discrepant findings between the present study and our previous adenoma study in Los Angeles (41). An interaction effect between XRCC1 genotype and smoking or alcohol on colorectal cancer risk is biologically plausible.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Therefore, the results observed in this study might be driven by this SNP, which was not investigated. A causal role of the codon 280 SNP and differences in LD patterns between Singapore Chinese and U.S. subjects also could explain the discrepant findings between the present study and our previous adenoma study in Los Angeles (41). An interaction effect between XRCC1 genotype and smoking or alcohol on colorectal cancer risk is biologically plausible.…”
Section: Discussioncontrasting
confidence: 94%
“…In contrast, a recent review of the literature concluded that the effect of smoking on risk of cancer might be modified by the XRCC1 genotype (40). Recently, we reported an XRCC1 genotype  smoking interaction effect on risk of colorectal adenomas in a Los Angeles sigmoidoscopybased study; the smoking effect was noted only among carriers of the Arg 194 -Arg 399 haplotype (41). Phenotype association studies suggest that both the XRCC1 codon 194 Trp and codon 399 Arg alleles are associated with higher repair proficiency (40), although functional studies have failed to find an effect for either SNP (42,43).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…13 An SNP in codon 399 was considered to be related to the DNA repair and was likely to exhibit an effect on the protein function. 14 Several studies have reported the association of XRCC1-399 with the risk in non-small-cell lung cancer (NSCLC), 15 colorectal cancer, 16 gastric cancer 17 and prostate cancer. 18 Additionally, reports in colorectal cancer patients show an improved survival for patients with XRCC1-399 G allele receiving 5-FU/oxaplatin chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The XRCC3 protein interacts with Rad51-related proteins in the process of homologous recombination. The C18067T (Thr241Met) variant of the XRCC3 gene in exon 7 modulates its function and is linked to an increased risk of bladder, breast, colorectal, lung and skin cancer [37][38][39][40][41]. Rad51 plays a crucial role in the HR pathway.…”
Section: Introductionmentioning
confidence: 99%